2016
DOI: 10.3389/fnhum.2016.00125
|View full text |Cite
|
Sign up to set email alerts
|

Lower Oxytocin Plasma Levels in Borderline Patients with Unresolved Attachment Representations

Abstract: Interpersonal problems and affective dysregulation are core characteristics of borderline personality disorder (BPD). BPD patients predominantly show unresolved attachment representations. The oxytocin (OT) system is associated with human social attachment and affiliative behavior, and OT dysregulation may be related to distinct attachment characteristics. Here, we investigated whether attachment representations are related to peripheral OT levels in BPD patients. Twenty-one female BPD patients and 20 age-, ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 77 publications
1
24
1
3
Order By: Relevance
“…There are several studies, however, that demonstrate the involvement of both ω-3 fatty acids and oxytocin in development. For example, higher levels of ω-3 fatty acids in maternal milk are associated with better temperament in children [157], and reduce negative affect and inflammation in children that have mothers with high levels of adiposity [158], while lower levels of oxytocin have been related to experiences of severe emotional neglect and abuse in childhood in plasma and cerebrospinal fluid samples [159,160]. Children raised in orphanages who experienced neglect have also been shown to have lower oxytocin plasma levels [161].…”
Section: Early-life Stress and Microglia: Clinical Studiesmentioning
confidence: 99%
“…There are several studies, however, that demonstrate the involvement of both ω-3 fatty acids and oxytocin in development. For example, higher levels of ω-3 fatty acids in maternal milk are associated with better temperament in children [157], and reduce negative affect and inflammation in children that have mothers with high levels of adiposity [158], while lower levels of oxytocin have been related to experiences of severe emotional neglect and abuse in childhood in plasma and cerebrospinal fluid samples [159,160]. Children raised in orphanages who experienced neglect have also been shown to have lower oxytocin plasma levels [161].…”
Section: Early-life Stress and Microglia: Clinical Studiesmentioning
confidence: 99%
“…As regards studies of peripheral concentrations of OT, it seems that serum OT is reduced in BPD, whereby the experience of childhood trauma, particularly emotional abuse and neglect, symptom severity, and aggressiveness correlated inversely with OT levels (Bertsch, Schmidinger, Neumann, & Herpertz, ). Lower OT levels were also associated with fears of compassion, recalled troublesome parenting, and with unresolved attachment representations (Ebert, Edel, Gilbert, & Brüne, ; Jobst et al , ). These findings are consistent with an association between lower OT levels in women reporting childhood abuse (Heim et al , ), a condition often found in patients with BPD.…”
Section: Nonverbal Synchronymentioning
confidence: 99%
“…OT in BPD exerts differential effects on fear, affiliation, and trust, as well as rejection sensitivity, whereby fear reduction is not paralleled by an increase in trust and prosocial behavior (Bartz et al., ; Brüne, Kolb, Ebert, Roser, & Edel, ; Ebert et al., ; Jobst et al., ). In addition, peripheral OT seems to be either generally lower in BPD patients than in controls (Bertsch, Schmidinger, Neumann, & Herpertz, ), or at least in a subgroup with unresolved attachment representations (Jobst et al., ). Lower OT levels have also been found in the cerebrospinal fluid of women with a history of traumatization (Heim et al., ).…”
Section: Introductionmentioning
confidence: 99%